Adapting A Design And Development Research (ddr) Approach In Designing The Mobile Application Model For Tarannum Subject - Nurul Auji Hasbullah; Norasikin Fabil; Adnan Mohamed Yusoff; Ahmad Sanusi Azmi (Universiti Tun Hussein Onn Malaysia Publisher’s, 2024)
Volume: 3 No: 2 (page: 193-204)